2013
DOI: 10.12681/mms.446
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and salinity variability in the Greek Seas based on POSEIDON stations time series: preliminary results

Abstract: Temperature and salinity time series provided by three POSEIDON monitoring stations (buoys) are examined in order to study the seasonal and interannual variability of the water mass characteristics. The sites at Athos (North Aegean Sea), E1M3A (Central Cretan Sea) and Pylos (Eastern Ionian Sea) were chosen, as these buoys provide measurements at various depths, while they represent 3 major basins respectively. The study of the T and S characteristics reveals important seasonal changes and highlights the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Whatever caused this salinity increase seems to follow an east to west direction. As argued in Velaoras et al [2013], the observed intermediate layer temperature and salinity increase may have originated in the Cretan Sea as a locally produced CIW with enhanced salinity, which reached the southeastern Ionian area through the Western Cretan Straits or may signify a thermohaline variation which influenced the intermediate layers (both LIW and CIW) in the whole eastern part of the EMed.…”
Section: Data Sets and Methodsmentioning
confidence: 71%
See 3 more Smart Citations
“…Whatever caused this salinity increase seems to follow an east to west direction. As argued in Velaoras et al [2013], the observed intermediate layer temperature and salinity increase may have originated in the Cretan Sea as a locally produced CIW with enhanced salinity, which reached the southeastern Ionian area through the Western Cretan Straits or may signify a thermohaline variation which influenced the intermediate layers (both LIW and CIW) in the whole eastern part of the EMed.…”
Section: Data Sets and Methodsmentioning
confidence: 71%
“…The Cretan Sea dataset comes from two different sources: (1) Velaoras et al [2013]. Apart from the wider time period covered, data used herein differ in that they are derived directly by the data loggers internal storing memory, while data in Velaoras et al [2013] are derived by the real-time transmission database.…”
Section: Data Sets and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Coastal location and season could influence the salinity of seawater, but generally the salinity of water from the Adriatic, Aegean and Ionian Seas are higher than the standard seawater. 14,15) The IAPSO standard seawater has 35.000 « 0.010 g/kg TDS.…”
Section: Introductionmentioning
confidence: 99%